DEVELOPMENT OF ARABIC-BASED LKPD AT MTS ISLAMIYAH GUNTING SAGA - Pane, Siti Sarah Sitorus; Zulheddi, Zulheddi (Academy of Education Journal, 2023)
This article aims to find out how to develop Arabic- based worksheets with the theme " اسرثئ " in increasing student learning interest at MTs Islamiyah Gunting Saga . This study uses a 4-D model; namely definition, design, development, and deployment. Sampling used a random sampling technique with class VIII A as the control class and class VIIIB as the experimental class with a total of 25 students. The results of this study state that the feasibility of Arabic- based LKPD with the theme " اسرثئ " is feasible to use through 2 expert validation tests, the feasibility of the module is seen from 2 components, namely material experts, and design. The validation results from the validator are: the average score of the content component is 7 9 , 1 7, and the presentation component is 82,55 . The score indicates a good/proper category, which means that the Arabic- based LKPD with the theme " اسرثئ " can be used with a little revision. The effectiveness of the Arabic -based LKPD with the theme " اسرثئ " can improve students' reading and writing Arabic skills when seen from the test results between the control class and the experimental class . Based on the results of data analysis, it can be concluded that Arabic- based worksheets with the theme " اسرثئ " can effectively improve students' reading, writing and language skills in class VIII MTs Islamiyah Gunting Saga in learning Arabic